Two Languages, Number One Authors: The Influence of Bilingual Upbringing on the Literary Accomplishments of Roald Dahl and Dr. Seuss - Ivana Marinić; Željka Nemet (ELOPE, 2008)
This paper focuses on the nature and impact of bilingual upbringing on cognitive development, thought and cultural experience of two bestselling authors, Roald Dahl and Theodor Seuss Geisel (Dr. Seuss). It argues that this bilingual upbringing resulted in a specific use of language in their literary accomplishments. Several segments from representative works by Dahl and Dr. Seuss are examined in order to reveal the stylistic particularities of the two authors, such as their original argot, word play, neologisms, the art of exaggeration and nonsense, as well as various aspects of metaphor. This is to show that bilingualism may be a decisive factor in creating a fruitful environment for the development of original and recognizable mode of written expression, which not only transcends cognitive and linguistic boundaries, but also cultural borderlines, resulting in the emergence of a new cultural artistic identity.